Comparative association between NAFLD and MAFLD with cardiovascular events and mortality: Evidence from observational studies. - Taoli Fu; Jitao Ling; Huilei Zhao; Kaixin Lin; You Deng; Miao Zhang; Xinrui Qi; Peng Yu; Weichun Lin; Xiao Liu (PLoS ONE)
Background Nonalcoholic fatty liver disease (NAFLD) and metabolic dysfunction-associated fatty liver disease (MAFLD) are increasingly recognized as multisystemic conditions with significant extrahepatic manifestations. Although both diseases have been linked to cardiovascular events and mortality, the strength of these associations remains controversial. This review aims to compare the risks of cardiovascular disease (CVD) events in individuals with NAFLD and MAFLD. Methods The PubMed, Embase, and Cochrane Library databases were searched to identify studies investigating the risk of CVD, CVD death, and all-cause death associated with NAFLD and MAFLD through April 28th, 2024. Data extraction and study quality assessment were performed using the Newcastle-Ottawa Scale. Statistical analysis utilized random-effects models. The quality of evidence was assessed using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) methodology. Results Eleven cohort studies with 11,995,994 patients were included. Both NAFLD and MAFLD were associated with an increased risk of cardiovascular events (NAFLD group vs. non-NAFLD group: HR = 1.30, 95% confidence interval (CI): 1.13-1.49, I2 = 91%; MAFLD group vs. non-MAFLD group: HR = 1.54, 95% CI: 1.32-1.81, I2 = 92%) and all-cause death (NAFLD group vs. non-NAFLD group: HR = 1.18, 95% CI: 1.04-1.33, I2 = 55%; MAFLD group vs. non-MAFLD group: HR = 1.30, 95% CI: 1.20-1.40, I2 = 0%). The MAFLD-only group had a stronger association with cardiovascular death than the NAFLD-only group (MAFLD-only group vs neither MAFLD nor NAFLD group: HR = 1.46, 95% CI: 1.40-1.51, I2 = 0%; NAFLD-only group vs neither MAFLD nor NAFLD group: HR = 1.10, 95% CI: 0.95-1.28, I2 = 0%, P for interaction < 0.01). The GRADE assessment revealed low certainty for cardiovascular disease (CVD) (NAFLD only group vs. neither NAFLD nor MAFLD group), cardiovascular death (NAFLD only group vs. neither NAFLD nor MAFLD group), and all-cause death (MAFLD group vs non-MAFLD group), and very low certainty for other results. Conclusion MAFLD and NAFLD are both associated with cardiovascular events and all-cause mortality. However, the odds of cardiovascular death seems to be greater in patients with MAFLD than in those with NAFLD, suggesting that the use of MAFLD criteria may identify more at-risk individuals. Prospero registration CD42022361164.